SOSIALISASI LINGKUNGAN HIDUP DAN PENGEMBANGAN PENDIDIKAN INTERATIF DI DESA BOCEK, KEC. KARANGPLOSO, KAB. MALANG - Dian Dwimitanti Nila Andini; Imam Musa Alfarozi; Purwaning Budi Lestari; Tri Asih Wahyu Hartati (JPM PAMBUDI, 2023)
Humans are social creatures, they need each other. Humans live within the scope of the organization and in groups. Various aspects of life in society greatly influence the quality of human resources but are balanced with the fulfillment of natural resources. These two components are the driving force as well as advancement in various aspects of life, namely education, culture, and the environment. These three elements complement each other. The most important aspect and a community need is education. Fun education needs to be held to create a generation that is able to build a better Indonesia. Education is a measure of the success of a learner depending on the strategy and media used.